Isolation of multidrug-resistant Escherichia coli from turkeys in Dinajpur, Bangladesh, and their antibiogram profile - Kundu, Tonmoy; Rumi, Nazmi Ara; Hossain, Md Khaled; Rahman, Md Shajedur; Hossain, Mirdha Md Kamal; Halder, Joyanta (Journal of Advanced Veterinary and Animal Research, 2021)
Objective: The study was carried out for molecular characterization and antibiotic resistance analysis of Escherichia coli isolated from different turkey farms in Dinajpur, Bangladesh. Materials and methods: A total of 45 samples comprising feces (n = 23) and cloacal swabs (n = 22) were collected randomly from turkeys. The samples were subjected to isolation and identification of E. coli by cultural and biochemical characteristics, followed by polymerase chain reaction and sequencing. An antibiogram of the isolated E. coli isolates was carried out by following the Kirby– Bauer disk diffusion method. Results: Out of the 45 samples, 28 (62.21%) were positive for E. coli, of which 16 (35.55%) fecal samples were positive and 12 (26.66%) cloacal swabs were positive . The antibiotic sensitivity analysis revealed that all the E. coli isolates were 100% sensitive to levofloxacin, norfloxacin, neomycin, gentamicin, and nitrofurantoin. On the other hand, all the isolates were 100% resistant to amoxicillin, azithromycin, erythromycin, tetracycline, bacitracin, cephalexin, nalidixic acid, vancomycin, methicilin, piperacillin, pefloxacin, novobiocin, cefepime, trimethoprim, netilmicin, and aztreonam. Conclusion: This study’s results uncover the occurrence and antibiotic resistance pattern of E. coli in the study area’s turkeys. J. Adv. Vet. Anim. Res., 8(1): 64-69, Mar 2021 http://doi.org/10.5455/javar.2021.h486